Air Pollution and Respiratory Permeability in Obstructive Sleep Apnea — A Review - Nguyen Thanh Tung; Hoang Ba Dung; Tran Phan Chung Thuy; Huynh Nguyen Xuan Thao; Hsiao-Chi Chuang (Aerosol and Air Quality Research)
Abstract Obstructive sleep apnea (OSA) is a common disorder characterized by recurrent episodes of nocturnal upper airway obstruction during sleep, which can seriously affect sleep quality and cause sleepiness during the daytime. Known risk factors for OSA are numerous, including obesity, age, gender, craniofacial anatomy, smoking, alcohol consumption, and genetic inheritance. Recently, air pollution was linked to an increased risk of OSA severity. Alterations in permeability are considered to be an important factor in the development of OSA; however, the role of air pollution remains unclear. This review article explored the role of air pollution and airway permeability in the pathogenesis of OSA.